PERTUMBUHAN DAN PRODUKSI JAGUNG (Zea mays L.) AKIBAT PEMBERIAN PUPUK SILIKA ORGANIK DAN TRICHOKOMPOS JERAMI PADI PADA TANAH INCEPTISOL - Serly Apriliya Oktariondari; Susilo Budiyanto; Budi Adi Kristanto (Fakultas Pertanian Universitas Muhammadiyah Tapanuli Selatan, 2023)
Inceptisols are immature soils where the profile development is still not perfect. This study pupose to determine the effect of organic silica fertilizer and rice straw trichocompost on the growth and production of maize on inceptisol soil. The study was begin from February 22 to August 14, 2021 at the Screenhouse of the Faculty of Animal and Agriculture, Diponegoro University, Semarang, while the analysis of soil, fertilizer and maize yields was carried out at the Laboratory of Physiology and Plant Breeding, Faculty of Animal and Agriculture, Diponegoro University, Semarang and the Laboratory of Integrated Gadjah Mada University, Yogyakarta. The design used was a 4 x 4 factorial trial with a completely randomized design (CRD) and 3 replications was used in this study. The first factor is the dose of organic silica fertilizer of rice husk ash (S) which consists of 4 levels, namely without organic silica fertilizer (S0), organic silica fertilizer 90 kg SiO2/ha (S1), silica fertilizer 180 kg SiO2/ha (S2) and organic silica fertilizer. silica 270 kg SiO2/ha (S3). The second factor is the dose of rice straw trichocompost (T), which consists of 4 levels, namely without rice straw trichocompost, 10 tons/ha, 20 tons/ha 30 tons/ha for T0, T1, T2 and T3. The research parameters consisted of organic matter and C-organic content, soil acidity, plant height, number of leaves, diameter and length of corn cobs, number of rows, weight of cobs with cob, weight of cobs without husks, dry weight of shelled corn and production per polybag which were then processed statistically using Analysis of Variance (ANOVA) to test the effect of treatment and if there was an effect of treatment, it was continued with Duncan's multiple distance test to see the difference between treatments at the 5% level. The results showed that there was no significant effect of organic silica fertilizer treatment on the parameters of plant height, number of leaves, diameter of the cob, length of the cob, number of rows of cobs, weight of cobs, weight of cobs without husks, production per polybag and dry weight of shelled corn. There was a significant effect of trichocompost treatment on the parameters of plant height, number of leaves, diameter of the cob, length of the cob, number of rows of cobs, weight of cobs, weight of cobs without shells, production per polybag and dry weight of shelled corn. The interaction between the dose 6,75 g SiO2/polybag and trichokompost 750 g/tanaman had a significant effect on the parameters of the soil analyst.